Experimental investigating of non-asbestos Automotive brake lining properties additional boric acid - Mutlu, Ibrahim; Çevik, Ismet; Öner, Cengiz (My University, 2002)
Brake lining which are used in Automotive disk are usually composed of various components. Studies to improve brake lining which doesn't contain asbestos have been increased due to the cancerogenic effects of asbestos which are used commonly. The value of brake lining have been kept low because of low price of asbestos used in high percentage in the composite. In this field it is necessary that the new materials must be low in price and could give same properties as asbestos. Boron and its compounds have been used in different area of industries. Boric acid is one of them. It is used in the production of glass fiber that is alternative material to supply fiber properties of asbestos, in the production of borglass to get thermal stability and used in ceramic industries to form hard surface against wear. Therefore, boric acid was added in brake lining component. The examples productions that contained boric acid or not were tested. The test result value have been plotted. The friction coefficient (?) and wear resist have been calculated from graphics. And also heat properties have been investigated in the case of time and load.
Borik asit katkili asbestsiz otomotiv fren balatasi özelliklerinin deneysel incelenmesi
Proceedings of the 3rd International Powder Metallurgy Conference -- 4 September 2002 through 8 September 2002 -- Ankara -- 62829
Keywords: Boric Acid; Brake Lining; Non Asbetos Brake Lining